2017
DOI: 10.22547/ber/9.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Upgrading in Pakistan’s Sporting Goods Industry in Global Value Chains: A Question of Progress?

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
(52 reference statements)
2
9
0
Order By: Relevance
“…What is most important in relation to the focus of this article is that recent efforts have also attempted to go beyond the discussion of 'economic' upgrading to also examine 'social' upgrading trajectories, and the interactions between the two (Barrientos et al, 2011, Barrientos et al, 2016, Lee et al, 2015. This research agenda is now expanding to unpack the environmental aspects of upgrading in GVCs, the relation between 'green business strategies' and GVC upgrading, and the effect that environmental upgrading has on further consolidation in GVCsas buyers can use it to extract concessions from suppliers (Jeppesen and Hansen, 2004, Ivarsson and Alvstam, 2011, De Marchi et al, 2013a, De Marchi et al, 2013b, Goger, 2013, Khattak et al, 2015, Khattak and Stringer 2017Krishnan, 2017). In this context, environmental upgrading is conceived as the process of improving the environmental impact of value chain operationsincluding production, processing, transport, consumption, and waste disposal or recycling.…”
Section: Environmental Upgrading In Gvcsmentioning
confidence: 99%
“…What is most important in relation to the focus of this article is that recent efforts have also attempted to go beyond the discussion of 'economic' upgrading to also examine 'social' upgrading trajectories, and the interactions between the two (Barrientos et al, 2011, Barrientos et al, 2016, Lee et al, 2015. This research agenda is now expanding to unpack the environmental aspects of upgrading in GVCs, the relation between 'green business strategies' and GVC upgrading, and the effect that environmental upgrading has on further consolidation in GVCsas buyers can use it to extract concessions from suppliers (Jeppesen and Hansen, 2004, Ivarsson and Alvstam, 2011, De Marchi et al, 2013a, De Marchi et al, 2013b, Goger, 2013, Khattak et al, 2015, Khattak and Stringer 2017Krishnan, 2017). In this context, environmental upgrading is conceived as the process of improving the environmental impact of value chain operationsincluding production, processing, transport, consumption, and waste disposal or recycling.…”
Section: Environmental Upgrading In Gvcsmentioning
confidence: 99%
“…Khattak et al [19] considered that GVCs represent both the drivers of environmental upgrading and the means by which to obtain the knowledge needed to upgrade, particularly for firms in relational networks. Khattak and Stringer [31] examined the impact of GVCs on the environment and claimed that through regular interaction, knowledge is created and transferred across the GVCs, resulting in environmental upgrading. Pathikonda and Farole [60] suggested that GVCs have altered the nature of Sustainability 2020, 12, 1237 4 of 26 global trade, and offer significant opportunities for developing countries to expand exports, access technology and raise productivity.…”
Section: Impacts Of Participation In Gvcs On Environment and Energy Cmentioning
confidence: 99%
“…Besides, participation in GVCs also means that the firms face differentiated and co-evolving environmental constraints and standards [29,30]. Supplier firms must comply with global standards and environmental certifications, which can cut down their carbon footprints, to avoid being excluded from GVCs [31][32][33][34]. Furthermore, participation in GVCs can lead to less raw material consumption and waste by extending product life [35,36].While some scholars have claimed that participation in GVCs leads to environmental degradation [37], the increase in participation in GVCs can increase energy consumption and CO 2 emissions due to several channels.…”
mentioning
confidence: 99%
“…inter alia, Barrientos & Smith, 2007;Bernhardt & Pollak, 2016;Ruwanpura & Wrigley, 2011), the relationship between economic and social upgrading (see, e.g., Barrientos et al, 2011;Barrientos et al, 2016), and the related 'value capture trajectories' (Coe and Yeung, 2015;Yeung and Coe, 2015;Neilson et al, 2018). However, only recently has an embryonic literature begun to look at the question of environmental upgrading in GVCs (see inter alia, Goger, 2013;Khattak & Stringer, 2017;Khattak et al, 2015;Ponte 2019).…”
Section: Economic and Social Upgrading: A Brief Reviewmentioning
confidence: 99%
“…The purchasing practices of lead firms – promoted by their sourcing departments – can involve squeezing product prices and demands for quick adaptation due to sudden or seasonal changes in demand. Last-minute orders, for example, can lead to lower wages, short-term or casual worker contracts, excessive overtime work (Lund-Thomsen and Lindgreen, 2014; Milberg and Winkler, 2013) and negative environmental consequences arising from suppliers taking shortcuts, for example when it comes to treating polluted water or securing the occupational health and safety of their employees (Goger, 2013; Khattak et al., 2015; Khattak and Stringer, 2017; Ponte 2019). At the same time, the sustainability departments of lead firms may require suppliers to increase worker wages, provide longer-term contracts and social insurance and/or meet environmental sustainability certifications.…”
Section: Introductionmentioning
confidence: 99%